REGIONAL GENERAL ELECTION COMMISSION STRATEGY IN OPTIMIZING THE LEVEL OF COMMUNITY POLITICAL PARTICIPATION IN REGIONAL HEAD ELECTIONS IN BANDUNG DISTRICT - Eko Novipratama; Nurliah Nurdin; Layla Kurniawati (Sean Institute, 2023)
This research explores the strategy of the Regional General Election Commission (KPUD) in increasing community political participation in regional head elections in Bandung Regency. The main focus is analyzing the steps taken by the KPUD to increase community involvement in the local democratic process. Qualitative methods with a case study approach were used to understand in depth the strategies implemented by the KPUD. The research results show that even though the KPUD has implemented various strategies, there are still several obstacles in optimizing community political participation. This research provides relevant insights for related parties to improve strategies and strengthen community political participation in regional head elections in Bandung Regency.